An Inducible Nitric Oxide Synthase Dimerization Inhibitor Prevents the Progression of Osteoarthritis - Xian Bo, Shang; Yan Jie, Wang; De Chao, Cai; Sai, Ma; Zhe, Wang; Ya Kun, Zhu; Hui Hui, Guo; Chen, Wang; Xiao, Ma; Zhong Yao, Hu; Hao Ran, Yu; Ji Sen, Zhang; et al. (Frontiers in Pharmacology, 2022)
Objective: Osteoarthritis (OA) is a degenerative joint disease. Excessive nitric oxide (NO) mediates the chondrocyte inflammatory response, apoptosis, and extracellular matrix (ECM) degradation during the occurrence and development of OA. NO in chondrocytes is mainly produced by inducible nitric oxide synthase (iNOS). The aim of this study was to design and synthesize an iNOS dimerization inhibitor and evaluate its effects on chondrocyte inflammation and articular cartilage injury in OA via in vitro and in vivo experiments. Design: The title compound 22o was designed, synthesized, and screened based on a previous study. The effects of different concentrations (5, 10, and 20 μM) of compound 22o on chondrocyte inflammatory response and ECM anabolism or catabolism were evaluated by Western blot and real-time quantitative reverse transcription-polymerase chain reaction using the rat chondrocyte model of IL-1β-induced OA. Furthermore, different doses (40 and 80 mg/kg) of compound 22o were administered by gavage to a rat OA model induced by anterior cruciate ligament transection (ACLT), and their protective effects on the articular cartilage were evaluated by histopathology and immunohistochemistry. Results: Compound 22o showed effective iNOS inhibitory activity by inhibiting the dimerization of iNOS. It inhibited the IL-1β-induced expression of COX-2 and MMP3 in the chondrocytes, decreased NO production, and significantly increased the expression levels of the ECM anabolic markers, ACAN, and COL2A1. Gavage with compound 22o was found to be effective in the rat OA model induced by ACLT, wherein it regulated the anabolism and catabolism and exerted a protective effect on the articular cartilage. Conclusions: Compound 22o inhibited the inflammatory response and catabolism of the chondrocytes and reduced articular cartilage injury in the rat OA model, indicating its potential as a disease-modifying OA drug.